Cytogenetic aberration in mixed-phenotype acute leukemia in children: A single-center retrospective review - Tsung-Yen Chang; Shih-Hsiang Chen; Tang-Her Jaing; Shu-Ho Yang; Yu-Chuan Wen; Chao-Ping Yang; Iou-Jih Hung (Pediatrics and Neonatology)
Background: Mixed-phenotype acute leukemia (MPAL) poses a diagnostic and therapeutic dilemma. No consensus exists on the strategy to assign patients with MPAL to either lymphoid- or myeloid-directed treatment. Thus, a better understanding of the characteristics of MPAL is a crucial unmet need. This study aims to provide information on a population-based cohort of children who received treatment based on standard, simple immunophenotypic criteria. Methods: Single-center, retrospective clinical and laboratory reviews of patients with MPAL were provided by morphology, immunophenotyping, cytogenetics, and molecular methods. We identified 242 flow cytometry samples. Of all consecutive pediatric patients with acute leukemia, we identified 8 (3.3%) patients with MPAL fulfilling WHO 2016 criteria; these were classified as follows: B-lymphoid + myeloid (n = 4), T-lymphoid + myeloid (n = 2), and B + T-lymphoid (n = 2). Results: Of 8 MPAL cases, 4 were boys and 4 girls [median age at diagnosis: 10.8 (range 1.1–17) years]. The b3a2 (p210) and e1a2 (p190) BCR/ABL fusion transcripts were detected in 1 patient with B/myeloid MPAL. Regarding the morphology, all patients were initially diagnosed as acute lymphoblastic leukemia, but no morphological characteristics or cytogenetic aberration was particularly predictive of an MPAL. Furthermore, 4 of 8 patients (50%) with MPAL were associated with chromosome 21 monosomy or partial trisomy. Conclusion: Despite no single recurrent chromosomal abnormality that could serve as a hallmark lesion in MPAL, cytogenetic alterations are frequent and predominantly associated with complex karyotype involving chromosome 21 abnormalities.